Identidade ticuna: (re)contextualizando as peças da coleção curt nimuendajú - (:unkn) unknown (Museu Paraense Emílio Goeldi, 2000)
This work focused on the Ticuna Collection of the "Curt Nimuendajú" Technical Reserve of the Museu Paraense Emílio Goeldi (MPEG). My objective was to analyze and contextualize the material culture/ritual life, as a fundamental instrument for the identity of the group. The Ticuna Collection consists of 444 artifacts collected by the ethnographer Curt Nimuendajú in 1941 and 1942 during fieldwork among these Indians, located in the upper Solimões River, in the state of Amazonas/Brazil, near the border with Colombia and Peru. The artifacts that make up the collection are directly or indirectly related to the Festa da Moça Nova. Thus, I worked, specifically, the artifacts that are part of the craft categories named by Berta Ribeiro (1988) as Ritual Dance Costume (mask) and Musical and Signaling Instruments, trying to demonstrate the importance of the Feast, (re)contextualizing the objects of the collection to understand the Magüta identity, those that were fished by Yoí.
Ticuna identity: (re)contextualizing the pieces of the Curt Nimuendajú collection
Keywords: Ticunas; Curt Nimuendajú; Coleção; CNPQ::CIENCIAS HUMANAS